Sustainable solid soap production using recycled cooking oil with ecoenzyme and lemongrass extract - Yusbarina; Zona Octarya; Elvi Yenti; Lisa Utami (Acta Biochimica Indonesiana, 2025)
Background: Improper disposal of used cooking oil poses significant environmental challenges, including groundwater contamination and harm to aquatic ecosystems. Recycling used cooking oil into solid soap offers a sustainable solution to reduce waste while creating a valuable, eco-friendly product. Objective: This study aims to produce solid soap from used cooking oil with the addition of ecoenzyme and lemongrass extract and evaluate its potential as an environmentally friendly and antimicrobial soap. Method: Used cooking oil was refined using bagasse as an adsorbent to remove impurities. Ecoenzyme was produced by fermenting organic kitchen waste, sugar, and water for three months, while lemongrass extract was prepared by blending and filtering lemongrass stalks. The soap was formulated by saponifying refined used cooking oil with NaOH, ecoenzyme, and lemongrass extract. The physical properties of the soap were assessed. Results: The resulting soap was solid, creamy in color, and emitted a refreshing lemongrass aroma. Antimicrobial properties are potential due to the organic acids and enzymes in the ecoenzyme, combined with the bioactive compounds in lemongrass extract. Conclusion: Solid soap made from used cooking oil with ecoenzyme and lemongrass extract offers a sustainable and effective solution for waste recycling while providing natural antimicrobial and cleaning benefits.